Prospective evaluation of chemotherapy-induced dyslipidemia in early breast cancer: implications for cardiovascular risk - Rusinova, Lenka; Medvedieva, Jelizaveta; Santova, Zuzana; Kozarova, Miriam (Frontiers in Oncology, 2026)
BackgroundCardiovascular disease is a leading cause of long-term mortality among breast cancer survivors, yet chemotherapy-induced dyslipidemia remains an underrecognized component of survivorship care.MethodsIn this prospective, single-center study, 56 women with clinical stage IB–IIIB early breast cancer received standardized anthracycline- and taxane-based chemotherapy. Fasting lipid profiles including low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), total cholesterol, and triglycerides, were assessed at four timepoints: baseline, post–anthracycline–cyclophosphamide phase, end of treatment, and 3-month follow-up. Longitudinal changes were analysed using non-parametric tests and multivariable linear regression.ResultsBaseline dyslipidemia was present in 78.4% of patients. Chemotherapy significantly altered all lipid parameters, with changes in total cholesterol (p = 0.004), LDL-C (p = 0.007), HDL-C (p < 0.001), and triglycerides (p = 0.002). The most pronounced alterations occurred during the anthracycline-based phase. Elevated LDL-C and reduced HDL-C levels persisted at follow-up. Lipid changes were not consistently associated with age, BMI, or menopausal status.ConclusionStandard chemotherapy induces sustained proatherogenic lipid shifts in women with early breast cancer, independent of baseline cardiovascular risk factors. The unexpectedly high prevalence of dyslipidemia among premenopausal women challenges traditional assumptions of cardiometabolic protection in younger patients. These findings support the integration of lipid monitoring and early cardiovascular risk management into survivorship care.Clinical Trial RegistrationNCT06958783, https://clinicaltrials.gov/study/NCT06958783.